Immunoglobulin Transporting Receptors Are Potential Targets for the Immunity Enhancement and Generation of Mammary Gland Bioreactor - Jiang, Xuemei; Hu, Jianjun; Thirumalai, Diraviyam; Zhang, Xiaoying (Frontiers in Immunology, 2016)
The functions of immunoglobulin transporting receptors (Ig transporting receptors) in immune system encompass from passive immunity to adaptive immunity by transporting immunoglobulins (Igs) and prolonging their half-life as well as enhancing immunosurveillance. Prior to the weaning, Ig transportations from mother to offspring confer the immediate passive immunity for neonates. After the weaning, FcRn and polymeric immunoglobulin receptor on infant intestinal epithelial cells retrieve Ig in intestinal lamina propria into the gut lumen for preventing pathogen invasion. This is not only improving the pathological consequences of infection but also helping the neonates for developing their own immune response; besides it would be the guidance for designing novel vaccines. Moreover, the investigations on Ig transporting receptors over-expressed transgenic animals have been carried out to improve Ig concentrations in serum and milk; thus, it would be a sustainable method to produce antibody-enriched milk-derived colostrum replacer for neonates. In order to generate mammary gland bioreactor, a series of methods have been developed for enhanced regulation of Ig transporting receptors expression and Ig transportation.